Risk factors for the onset of arterial hypertension in women of the first adulthood in the period of manifestation of the disease - Рубан, Лариса (Slobozhanskyi Herald of Science and Sport, 2018)
Larysa Ruban Purpose: to carry out lifestyle studies of women of 35–40 years with the manifestation of arterial hypertension. Material & Methods: the results of answers of 65 women aged 35–40 with the manifestation of arterial hypertension were analyzed using the questionnaire "Subjective assessment of lifestyle and physical health". Results: only 42% of women lead a healthy lifestyle and their health status can be assessed as good. Indicators of 33% of women say that the state of health is still good and the way of life is close to healthy. In 17% of women, the state of health can be assessed as satisfactory, but the lifestyle requires change. And in 8% of women the attitude to HLS can be assessed as unsatisfactory, that is, these women have a disregard for their own health. Conclusions: the test contingent of women and mature age there is an increase in body weight, lack of physical activity, non-compliance with diet, the presence of bad habits, which requires appropriate lifestyle adjustments and optimization of physical activity.